Highly Conductive Films Through PEDOT‐PSS Ink Formulation via Doping Using Spontaneous Wicking of Liquids for Supercapacitor Applications - Melkie Getnet Tadesse; Nicolai Simon; Jörn Felix Lübben (Advanced Energy & Sustainability Research, 2024)
A novel electrode fabrication method based on liquid doping of PEDOT‐PSS onto PET‐G film by drop casting is reported. A dispersed liquid‐PEDOT‐PSS solution is prepared as an ink by a liquid doping synthesis method. The EG/DMSO:PEDOT‐PSS solution is then drop cast onto oxygen plasma‐modified PET‐G films for electrode fabrication. Their surface topography and electrochemical characteristics are characterized. The results show that the prepared electrode material has an electrical conductivity of 11661.7 and 11528.8 S m−1 for EG‐ and DMSO‐treated PEDOT‐PSS films, respectively. Ink formulation achieves unprecedented conductivity via spontaneous liquid wicking. The specific capacitance is 134 F g−1 at a scanning rate of 5 mV s−1 and 309.6 F g−1 at a scanning rate of 20 mV s−1 for EG and DMSO‐treated PEDOT‐PSS films, respectively, on the three‐electrode system while specific capacitance for pristine PEDOT‐PSS calculated at 80 mV s−1 is 4.6 F g−1. PEDOT‐PSS films are engineered for superior supercapacitor performance through liquid wicking. Moreover, the results of Fourier‐transform infrared spectroscopy (FTIR), atomic force microscopy (AFM), and Raman spectroscopy measurements confirm that the removal of PSS on the surface is due to liquid–liquid doping. Energy‐dispersive X‐ray spectroscopy analysis proves the expulsion of PSS molecules from the solution interface. Therefore, the die‐cast PET‐G‐PEDOT‐PSS electrode is a promising candidate for advanced supercapacitor applications.